Stereoselective nickel-catalysed arylative cyclisation reactions - Panchal, Heena (2019)
Chapter 1: Indanes and their derivatives are a common unit in a range of biologically active scaffolds. Numerous approaches have been reported for the synthesis of these scaffolds. Annulation reactions between ortho-functionalised aryl aldehydes or ketones with various unsaturated reaction partners provide a useful approach towards indenols. Herein, the synthesis of 3-methyleneindan-1-ols using nickel catalysis is reported. The reaction between activated allenes and 2-acylarylboronic acids generates the products in generally good yields and excellent diastereoselectivities. This methodology allows access to products with fully substituted olefins, and adjacent quaternary centres. The reaction can be effectively scaled up, the catalyst loading decreased, and enantioselectivity can be induced via the addition of a chiral ligand.